(untitled) (Research, Society and Development, 2021)
Civil construction is responsible for a high rate of environmental impact caused by unaware consumption of raw materials. Among the most depleted natural resources are river sands that are being replaced by sand from rock crushing. The use of this type of sand with adequate procedures can be a viable alternative for the substitution of natural sand in the production of coating mortar. In bibliographical references, information involving analyses about the use of crushed sand from limestone and basalt rocks are found, and few involving sand from granite rocks, a residue produced in large scale in the southern region of Rio Grande do Sul, especially in regions of granite extraction, such as the city of Capão do Leão. Considering these facts, in the present work, an analysis of the use of a crushed sand of granite origin in partial (50%) and total (100%) substitution of the natural sand of a coating mortar, produced with the mix 1:1:6 (cement, lime and sand, respectively), was carried out. The analysis aimed at verifying the influence of the granite sand grain characteristics on the coating mortar properties. The sands used were analyzed for grain size, specific mass, unit mass, mineralogy, absorption and grain shape. The mortars with natural sand and with granite sand were analyzed in the fresh state for the consistency index, and in the hardened state for capillary absorption, axial compressive strength, and three-point flexural tensile strength.